Peran Kepala Madrasah dalam Meningkatkan Kinerja Guru di MIN 3 Demak - Muhammad Ahsanul Fikri; Wahyudi Wahyudi (Jawda: Journal of Islamic Education Management, 2021)
The head of the madrasa is a figure who has a big role in running the wheel of the educational organization. The head of the madrasa in the organization is needed to bring organizations to the established objectives. The increase in teacher performance is a about who determines the success of the school / madrasa institution, because from the teachers of changes in the education sector will be achieved. The teacher's factor really determines the formation of quality students. Therefore the role of the madrasa head is needed in order to help teachers to be more professional. The purpose of this study was to be able to find out: (1) to describe the role of the Madrasah Chief of Improving Teacher's performance in MIN 3 Demak (2) to describe the strategy used by the Madrasah Head in Improving Teacher's performance in MIN 3 Demak (3) to describe the constraints and solution of the head of the madrasa in improving teacher performance in MIN 3 Demak. This study uses a qualitative approach. The techniques used in research are observation, interviews, and documentation. Then the data obtained was analyzed by: data reduction, data presentation, and conclusion withdrawal. The results of this study indicate that: (1) the role of the madrasa head in improving teacher performance in MIN 3 Demak is a) head as an educator, b) as a supervisor, c) as a motivator. (2) The strategy used by the head of the Madrasah in improving teacher performance in MIN 3 Demak is a) Discipline, c) Motivation, c) Provision of Rewards and Punishment, d) Training Activities, e) Evaluation. (3) Constraints and Solutions Head of Madrasah In Improving Teacher's Performance in MIN 3 Demak is a) Lack of Facilities and Infrastructure, b) Mastery of Material, c) There are still several educators who are less disciplined. With solutions to strive to meet the facilities and infrastructure needed, including teachers in training and workshops, giving warning and always reminding the importance of behavior of discipline.